2012
DOI: 10.1095/biolreprod.111.096719
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3-Initiated Antiviral Responses in Mouse Male Germ Cells In Vitro1

Abstract: The testis is an immunoprivileged site where local cell-initiated innate immunity plays a crucial role in antimicrobial responses. Toll-like receptors (TLRs) mediate innate immune responses in testicular somatic cells. Although several TLRs are expressed in some stages of male germ cells, the potential role of TLRs in triggering antimicrobial responses in the germ cells has yet to be exclusively studied. The current study demonstrates that TLR3 is constitutively expressed in spermatogonia and spermatocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 52 publications
0
34
0
1
Order By: Relevance
“…105 We recently demonstrated that TLR3 in spermatogonia and spermatocytes and TLR11 in spermatids initiate innate immune responses. 108,109 The TLR-initiated innate immune responses in male germ cells are particularly interesting because the germ cells represent a majority of the testicular cell population. Moreover, the adluminal compartments of the seminiferous tubules are separated from the interstitial immune components by the BTB.…”
Section: Tlrs In Testicular Cellsmentioning
confidence: 99%
“…105 We recently demonstrated that TLR3 in spermatogonia and spermatocytes and TLR11 in spermatids initiate innate immune responses. 108,109 The TLR-initiated innate immune responses in male germ cells are particularly interesting because the germ cells represent a majority of the testicular cell population. Moreover, the adluminal compartments of the seminiferous tubules are separated from the interstitial immune components by the BTB.…”
Section: Tlrs In Testicular Cellsmentioning
confidence: 99%
“…Mouse Sertoli cells express TLR2 to TLR5, which can be activated by their respective PAMPs (Riccioli et al, 2006;Starace et al, 2008;Sun et al, 2010;Winnall et al, 2011;Wu et al, 2008). Expression, as well as activation, of TLR3 and TLR4 in mouse Leydig cells, and TLR3 in male germ cells were recently demonstrated (Shang et al, 2011;Wang et al, 2012). These studies have suggested that TLRs in the testicular cells play a role for the testis to mount appropriate local responses to invading microbial antigens.…”
Section: Introductionmentioning
confidence: 97%
“…Collectively, these MIXinduced changes in mRNA content suggest biochemical changes that could decrease the systemic androgen/estrogen ratio. Although not found by RT-PCR analysis, microarray analysis indicated that the expression of mRNA for TLR3 was also decreased in the testis of calves born to MIXsupplemented dams, which would further exacerbate an androgen to estrogen shift, as activation of the TLR3 receptor is responsible for triggering the testicular innate immune response, decreasing circulating concentrations of testosterone [44,45]. Although speculative, increased expression of mRNA for CDK5R1 in the testis of calves born to MIXdams may reflect a compensatory mechanism to maintain the testis ability to produce sufficient testosterone.…”
Section: Discussionmentioning
confidence: 88%